Reactive Nodular Fibrous Pseudotumor of Abdominal Cavity: A Non-neoplastic Mimic of Malignant Mesenchymal Tumors - Todi, Richa; Krishna, M Sunil; Shenoy, K. Rajgopal; Bhat, Chitra Y; Kumar, M Keerthan (Medical Science: Trends and Innovations Vol. 13, 2025)
Reactive nodular fibrous pseudotumor (RNFP) is a recently described mesenchymal lesion arising from the gastrointestinal tract, mesentery, or retroperitoneum, which, although mimicking malignancy, is a non-neoplastic reactive process. It is a rare entity with only a few cases reported in literature so far, and is less aggressive when compared to other mesenchymal lesions such as gastrointestinal stromal tumour (GIST) or fibromatosis. It represents one spectrum of the heterogeneous group of abdominal mesenchymal tumours that pose a diagnostic dilemma to both the surgeons and the pathologists. Distinguishing between them is essential as their treatment and prognosis vary widely. Correct diagnosis is of paramount importance for proper treatment. Here, this study presents one such case in a 20-year-old female who presented with a huge abdominal mass. Contrast-enhanced computed tomography showed a well-defined heterogeneously enhancing soft tissue mass in the left retroperitoneum, probably arising from the pancreas. The radiological diagnosis was of a pseudopapillary tumour of the pancreas. The patient underwent exploratory laparotomy and excision of the mass in toto along with sleeve gastrectomy and splenectomy. However, post-operative histopathology was consistent with Reactive nodular fibrous pseudotumor. The patient was followed up at 1, 6, and 12 months. After 1 year, the patient was asymptomatic with no evidence of recurrence of the tumour. This case illustrates the need for keeping RNFP in mind as a differential diagnosis in a case of a large abdominal mass, as it has a fairly good prognosis with no reported recurrence after surgical excision.